Pemberdayaan Lansia Melalui Kegiatan Senam Dan Storytelling Untuk Mewujudkan Lansia Sehat Dan Produktif - Sri Ariyanti; Surtikanti Surtikanti; Tri Wahyuni (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Empowering the elderly is one of the important efforts in improving their quality of life and welfare in old age. The elderly are among the age groups that are vulnerable to experiencing a decline in physical, mental, and social conditions due to the aging process. Therefore, a holistic and sustainable approach is needed to support their health and quality of life. One of the activities that has proven effective is elderly gymnastics which can maintain body fitness, improve blood circulation, improve flexibility, balance, and reduce the risk of falling. Gymnastics can also help control blood pressure in the elderly with hypertension. On the other hand, storytelling activities provide great benefits to the mental and emotional health of the elderly. This activity can train memory, stimulate cognitive abilities, build confidence, and strengthen social relationships with others. Through sharing stories, seniors feel more valued, listened to, and have the opportunity to express their life experiences. Community Service Activities (PKM) in the Korpri Health Center Work Area aim to improve the physical, social, mental, and emotional health of the elderly through the Plan-Do-Check-Act (PDCA) approach. Before the activity starts, vital signs such as blood pressure, pulse, breathing, and body temperature are measured. The results of the examination showed that 20 out of 25 participants (80%) had hypertension with an average systolic blood pressure of 155.12 mmHg and diastolic 103.80 mmHg. After the examination, all the elderly took part in a gymnastics session guided by health center officers. The activity ended with a storytelling session, where 90% of the participants were able to remember events 20 years ago. These findings show the importance of regular check-ups, physical activity, and social interaction as preventive measures to improve the quality of life of the elderly. Storytelling has also been shown to strengthen emotional and social bonds among the elderly.